Proline and Antioxidant Enzyme Activities in Some Strawberry Cultivars under Drought and Recovery - Gülen, Hatice; Kesici, Müge; Çetinkaya, Cem; Ergin, Sergül (UNIV AGR SCI & VETERINARY MED CLUJ-NAPOCA, 2018)
This study examines the molecular effects of drought and recovery applications on four strawberry (Fragaria x ananassa Duch) cultivars known as relatively heat-tolerant ['Redlands Hope' ('R. Hope') and 'Camarosa'] and heat-sensitive ['Festival' and 'Cal. Giant-3' ('CG-3')]. After frigo seedlings were grown in a greenhouse for eight weeks (until they had five-six leaves) in a pot, 10% Poliethyleneglycol 6000 (PEG) was applied in order to compose drought condition for 15 days. Following PEG application, plants were watered without PEG for 15 days to observe the recovery. Leaf relative water content (RWC), loss of turgidity, cell membrane injury, proline content and the activities of ascorbate peroxidase (APX, EC 1.1.11.1), glutathione reductase (GR, EC 1.6.4.2) and peroxidase (PRX, EC 1.11.1.7) were determined in leaf tissues taken from plants at the end of the drought and recovery applications. Although membrane injury was increased by the PEG application, it reduced almost to the control levels at the end of the recovery period. Proline contents were found higher in cvs. 'R. Hope' and 'Camarosa' than cvs. 'Festival' and 'CG-3' under drought conditions. APX and GR enzymes showed great activities in drought applied plants of heat-tolerant cultivars. Native polyacrylamide gel electrophoresis (PAGE) of basic PRX isozymes yielded three protein bands with Rf = 0.45, Rf = 0.55 and Rf = 0.60 that were sharply increased their activities by PEG and recovery applications in cvs. 'R. Hope' and 'Camarosa'. In addition, leaves of all cultivars exposed to drought rolled up and had brown colour in various level as an indication of tolerance. Indeed 'Camarosa' and 'R. Hope' showed better recovery performance after rewatering than 'Festival' and 'CG-3'. All data indicated that heat-tolerant cultivars showed relatively drought tolerance in this study.
Keywords: antioxidative enzymes; drought; Fragaria x ananassa Duch; PEG; recovery